Clinical management of patients with septic shock in the Intensive Care Unit (Research, Society and Development, 2022)
Septic shock is considered a potentially serious clinical condition due to a dysregulated inflammatory response in the body. The disease is the leading cause of hospitalization worldwide and the leading cause of death in intensive care units, causing long-term suffering to patients and their families. This study is justified by the fact that septic shock is characterized as a disease that causes more deaths in the hospital environment, specifically in the Intensive Care Unit. Thus, the objective of the present study focuses on identifying the clinical management of patients with septic shock in the Intensive Care Unit. To carry out the study, an integrative literature review was carried out. Some important points were identified regarding the main care and clinical management performed to the patient diagnosed with sepsis. Based on this principle, the multiprofessional team has an essential role in the care and performance of adequate assistance according to the needs and particularities of each individual, for this, it is extremely important that a care plan is built by the professional team. The clinical characteristics and diagnosis of the patient must be investigated before drawing up any plan, however, life support must be initiated in the first instance to avoid any aggravation or risks to the patient's life. In this sense, monitoring vital signs stands out as the primary care provided by professionals, as patients with septic shock have several oscillations in their health status.